Performance analysis of downlink scheduling in 3GPP LTE system / Muhammad Haikal Hashim - Hashim, Muhammad Haikal (2014)
In this report an overview of the Long Term Evolution (LTE) is presented. LTE is the new revolution of wireless technology especially in cellular 4G services. The service allows mobile users to access Internet through their devices. LTE intends to deliver higher speed data and multimedia services for the next generation. In coming years, LTE technology will be widely used by people on their devices such as notebooks, smartphones, gaming devices and video cameras. LTE technology is a based on 3GPP standard and provides downlink speed up to 150 megabits per second (Mbps) and an uplink speed of up to 50 Mbps, and both using 20 MHz bandwidth. LTE is the new way for cellular communications to operate at higher data rate, achieving 100 Mbps or faster. LTE also support a low latency of 10ms round trip delay, improves system capacity and coverage and reduces operating costs. Furthermore, it supports Multiple Input Multiple Output (MIMO) and allows continuous integration with existing systems. A scheduler assigns the shared resources (time and frequency) among users terminals. In this thesis, the focus is on the downlink scheduling. The Round Robin, Best CQI and Proportional Fair scheduling algorithm have been considered in this report. All the implementation, analysis and comparison of these scheduling algorithms were done through simulations executed on a MATLAB-based downlink link level simulator, Vienna LTE Simulator